The influence of word wall media toward hospitality students’ vocabulary mastery - Putu Sri Darmayanti; Ni Made Sri Rahayu (Universitas PGRI Madiun, 2023)
As a foreign language, English is not easy to be mastered by the students. There is still dissatisfaction with the English proficiency of Indonesian students. Many students find difficult to write and speak English in a simple sentence. It makes the students feel less confidence, afraid of made some mistake, and memorizing word is quite bored to be learned. Lack of vocabulary felt by Indonesian students make them difficult to understand spoken and written language. English proficiency among Indonesian students’ needs more improvement to assist them to communicate effectively. The technology provides many resources suitable to utilize as a media in teaching and learning process. The researcher implemented word wall media as a tool to teach vocabulary, letter-sound correspondence, spelling, etc. It is a good way to make the activity in the classroom becomes more fun and interesting in hospitality students at Institut Pariwisata dan Bisnis Internasioanal. This study used a qualitative approach by implementing a case study design. The questionnaire and the interview sheet given to the 61 respondents. The result show that most students increase their vocabulary mastery. 67,2% students agree that the word wall media helped to understand the vocabulary easily, 77% students easy to understand the vocabulary with picture include, 54,1% students enjoyed the activity in the classroom, 54% students mentioned that the word wall media was easy to use, and 60,7% students mentioned that they could memorize longer.